Autophagy in Viral Development and Progression of Cancer - Suares, Alejandra; Medina, María Victoria; Coso, Omar (Frontiers in Oncology, 2021)
Autophagy is a complex degradative process by which eukaryotic cells capture cytoplasmic components for subsequent degradation through lysosomal hydrolases. Although this catabolic process can be triggered by a great variety of stimuli, action in cells varies according to cellular context. Autophagy has been previously linked to disease development modulation, including cancer. Autophagy helps suppress cancer cell advancement in tumor transformation early stages, while promoting proliferation and metastasis in advanced settings. Oncoviruses are a particular type of virus that directly contribute to cell transformation and tumor development. Extensive molecular studies have revealed complex ways in which autophagy can suppress or improve oncovirus fitness while still regulating viral replication and determining host cell fate. This review includes recent advances in autophagic cellular function and emphasizes its antagonistic role in cancer cells.